Untreated Hypertension: A Powerful Risk Factor for Lobar and Non-Lobar Intracerebral Hemorrhage in Whites, Blacks, and Hispanics - Walsh, Kyle B. (Circulation, 2016)
BACKGROUND: Hypertension is a significant risk factor for intracerebral hemorrhage (ICH). While ethnic/racial disparities related to hypertension and ICH have been reported, these previous studies were limited by a lack of Hispanics and inadequate power to analyze by ICH location. In the current study, while overcoming these prior limitations, we investigated whether there was variation by ethnicity/race of treated and untreated hypertension as risk factors for ICH. METHODS: The Ethnic/Racial Variations of ICH (ERICH) study is a prospective, multicenter, case-control study of ICH among whites, blacks, and Hispanics. Cases were enrolled from 42 recruitment sites. Controls matched to cases 1:1 by age (±5 years), sex, ethnicity/race, and metropolitan area were identified by random-digit dialing. Subjects were interviewed to determine history of hypertension and use of anti-hypertensive medications. Cases and controls within ethnic groups were compared using conditional logistic regression. Multivariable conditional logistic regression models were computed for ICH as an overall group and separately for the location subcategories deep, lobar, and infratentorial (brainstem/cerebellar). RESULTS: 958 white, 880 black, and 766 Hispanic ICH cases were enrolled. For ICH cases, untreated hypertension was higher in blacks (43.6%, p<0.0001) and Hispanics (46.9%, p<0.0001) versus whites (32.7%). In multivariable analyses adjusted for alcohol use, anticoagulation, hypercholesterolemia, education, and medical insurance status, treated hypertension was a significant risk factor across all locations of ICH in whites (odds ratio [OR] 1.57, 95% CI 1.24–1.98, p<0.0001), blacks (OR 3.02, 2.16–4.22, <0.0001), and Hispanics (OR 2.50, 1.73–3.62, <0.0001). Untreated hypertension was a substantially greater risk factor for all three racial/ethnic groups across all locations of ICH: whites (OR 8.79, 5.66–13.66, <0.0001), blacks (OR 12.46, 8.08–19.20, <0.0001), Hispanics (OR 10.95, 6.58–18.23, <0.0001). There was an interaction between race/ethnicity and ICH risk (P<0.0001). CONCLUSIONS: Untreated hypertension confers a greater ICH risk in blacks and Hispanics relative to whites across all anatomic locations of ICH. Accelerated research efforts are needed to improve overall hypertension treatment rates and to monitor the impact of such efforts on racial/ethnic disparities in stroke.